1999
DOI: 10.1161/01.cir.99.17.2268
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone Interaction With β-Blockers

Abstract: the EMIAT and CAMIAT InvestigatorsBackground-Investigations with in vitro and animal models suggest an interaction between amiodarone and ␤-blockers.The objective of this work was to explore if an interaction with ␤-blocker treatment plays a role in the decrease of cardiac arrhythmic deaths with amiodarone in patients recovered from an acute myocardial infarction. Methods and Results-A pooled database from 2 similar randomized clinical trials, the European Amiodarone Myocardial Infarction Trial (EMIAT) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
7

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(30 citation statements)
references
References 12 publications
(12 reference statements)
0
23
0
7
Order By: Relevance
“…However, the OPTIC study demonstrated the additional benefit of amiodarone in combination with beta‐blockers for preventing future ICD interventions in those with inducible or spontaneous ventricular tachyarrhythmias 32. Nonetheless, previous reports were frequently confounded by a nonuniform patient population 33, 34. One of the randomized trials demonstrated that the mortality and quality of life in NICM patients with a reduced LVEF were similar between those receiving amiodarone, and those with an ICD implantation for nonsustained VT 3.…”
Section: Management Of Vt In Nicmmentioning
confidence: 99%
“…However, the OPTIC study demonstrated the additional benefit of amiodarone in combination with beta‐blockers for preventing future ICD interventions in those with inducible or spontaneous ventricular tachyarrhythmias 32. Nonetheless, previous reports were frequently confounded by a nonuniform patient population 33, 34. One of the randomized trials demonstrated that the mortality and quality of life in NICM patients with a reduced LVEF were similar between those receiving amiodarone, and those with an ICD implantation for nonsustained VT 3.…”
Section: Management Of Vt In Nicmmentioning
confidence: 99%
“…Subgroup analysis of AMD in post-myocardial infarction trials has suggested that AMD is particularly effective when used with a -blocker. 21) If a -blocker was more frequently used in the AMD group in the present study, then hemodynamic measurements in the AMD group might be expected to improve during follow-up. On the other hand, it has been reported that AMD monotherapy resulted in a substantial increase in left ventricular systolic function in patients with congestive heart failure (LVEF < 40%).…”
Section: Hemodynamicsmentioning
confidence: 80%
“…Only the combination of amiodarone and beta-blockers has shown some efficacy in reduction of SCD (19).…”
Section: Discussionmentioning
confidence: 99%